Stroke Incidence and Risk Profile in Misrata City: A Retrospective Cross-Sectional Hospital-Based Study from Emergency Medical Records (2019–2020) (مجلة الرازي الطبية, 2025)
A stroke significantly affects both individuals and their communities. Understanding the epidemiology and occurrence of strokes within a community can enhance awareness and guide treatment strategies to reduce their immediate and long-lasting effects. Our objective is to identify the epidemiological factors and accompanying comorbid conditions linked to stroke among patients visiting the Emergency Department at Misrata Medical Centre MED. This is a hospital-based retrospective cross-sectional design study that includes patients of any sex presenting with an acute cerebral vascular accident (CVA) at the medical emergency department (MED) at Misrata Medical Center (MMC) during the period from January 1, 2019, to December 31, 2020. All medical records with a diagnosis of stroke were identified based on the definitions provided by the International Classification of Diseases. Among 837 stroke patients seen at Misurata MED (2019–2020), 440 had acute strokes and 397 had old strokes, with an average annual incidence of 461.95 per 100,000 MED patients and 33.14 per 100,000 city population. Males accounted for 61.05% of cases (p < 0.0001). Stroke incidence peaked at age 70–79 (22.6%) and showed a significant age-sex association (p < 0.0001). Polynomial regression (R² ≈ 0.878) indicated a strong non-linear relationship with age. Ischemic strokes dominated (90.45%). Risk factors were present in 76% of cases; hypertension was most common (59.1%), often combined with diabetes (25.9%). Stroke risk was significantly higher in patients with multiple risk factors (p < 0.0001), and hypertension increased stroke risk by 3.5 times compared to other risk profiles. Stroke incidence at Misrata Medical Centre is notably high, particularly among older males, with ischemic stroke being the predominant type. The findings highlight hypertension and diabetes as the most prevalent and impactful risk factors, especially when combined. The significant association between multiple risk factors and increased stroke likelihood underscores the urgent need for targeted prevention, early screening, and comprehensive management strategies, particularly in high-risk populations. These insights can guide local health policies to reduce stroke burden and improve patient outcomes.